The Economic Potential of Smoking Cessation Interventions at the Point of Diagnosis of Non–Small Cell Lung Cancer - Mari Jones (Value in Health, 2023)
Stopping smoking has proven benefits in nearly all illnesses but the impact and health economic benefits of stopping smoking following a diagnosis of lung cancer are less well defined. We assessed the cost-effectiveness of smoking cessation (SC) services for newly diagnosed lung cancer patients against current usual care, where patients are unlikely to receive SC service referral. A health economic model was constructed in Excel. The modelled population comprised patients with a new diagnosis of non-small-cell lung cancer (NSCLC). Data from the LungCast dataset (Clinical Trials Identifier NCT01192256) were used to estimate model inputs. A structured search of published literature identified inputs not represented in LungCast, including healthcare resource use and costs. Costs were estimated from a 2020/21 UK NHS and Personal Social Services (PSS) perspective. The model estimated the incremental quality-adjusted adjusted life year (QALY) gained in newly diagnosed NSCLC patients receiving targeted SC intervention compared to those receiving no intervention. Extensive one-way sensitivity analyses (SA) explored input and dataset uncertainty.Results: In the five-year base-case, the model estimated an incremental cost of £14,904 per QALY gained through SC intervention. Sensitivity analysis estimated an outcome range of between £9,935 and £32,246 per QALY gained. The model was most sensitive to the estimates of relative quit rates and expected healthcare resource use.